Sistem Informasi Manajemen dan Loyalitas Pengguna Jasa pada Industri Maritim di Indonesia - Zebua, Monazatulo; Suhalis, Adenan; Raga, Paulis; Sonny, Imam; Majid, Suharto Abdul (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The purpose of this study was to determine the contribution of ship agency service quality and management information systems to service user loyalty through internal control mediation at Tanjung Priok Port. Some of the problems found, among others, are still not optimal service quality and management information systems provided by the company to customers. In addition, internal control has not been carried out optimally and ship departure schedules are sometimes not as promised by the company. This research was conducted at PT Umbu Perdana Maritim as a new agency company located in the Tanjung Priok Port area. The research population is the customers of PT Umbu Perdana Maritim, for a sample of 60 active customers which is called a saturated sample. For data processing carried out in this study, using the path analysis method. The results showed that the quality of ship agency services did not have a direct effect on service user loyalty through internal control, and the management information system did not have a direct effect on service user loyalty through internal control.